Identification of Fetal Growth Restriction in Pregnant Women With Prior Bariatric Surgery [16K]. (May 2020) - Cruz, Meredith; Harrison, Rachel; Allen, Katherine; Braun, Emilie; Semons-Booker, Kia; Wlodarczyk, Katarzyna
Abstract : INTRODUCTION: Scant formal guidelines exist regarding antenatal ultrasounds in pregnant women with prior bariatric surgery. Considering rates of small-for-gestational-age (SGA) infants may be increased, we investigated whether antenatal ultrasounds were predictive in this population compared to controls. METHODS: Women with prior bariatric procedures were matched to controls by early pregnancy body mass index (BMI). 182 women with prior bariatric procedures and 190 controls were identified and the frequency of prenatal fetal growth restriction and postnatal SGA were examined. Sensitivity, specificity, and area under the curve (AUC) for diagnosis of SGA were calculated for both groups. RESULTS: Among all women with prior bariatric surgery, 116 (63.7%) had two or more ultrasounds after anatomic survey compared to 89 (46.3%) controls. The average BMI in both groups was 35.3 kg/m 2 . Out of 19 infants found to be SGA at birth in the bariatric procedure group, 7 were diagnosed prenatally. Out of 21 infants with SGA in the control group, 6 were diagnosed prenatally. When analyzing women who had 2 or more ultrasounds after anatomic survey specifically, the sensitivity was 35.3% for prior bariatric surgery and 54.5% for controls. Specificity was greater than 98.5% for both groups. AUC for two or more ultrasounds was 0.766 (95% CI 0.61-0.92) for controls and 0.689 (95% CI 0.57-0.81) for prior bariatric surgery, P= .436. CONCLUSION: Sensitivity for diagnosis of SGA is low in women with prior bariatric surgery, but is not different when compared to BMI-matched controls. The low sensitivity is likely a product of elevated BMI in both groups.